Tata Laksana Pengelolaan Pakan Sapi Potong - D Ardiansyah; N Irwani; Y Priabudiman (Politeknik Negeri Lampung, 2019)
Cattle fattening in Indonesia use a dry lot fattening system, which is a fattening system in a cage, and the feed is rationed or served. The feed has a high contribution of around 75% in production costs. The purpose of this Final Project Report is to understand the feed management of beef cattle at PT Indo Prima Beef. Data was collected using interviews, observation, and library methods. Feed planning is done 2 times, in the morning ± 06.00 to see the consumption of the night and during the day ± 13.00 to see the morning consumption. Feed distribution at PT Indo Prima Beef is divided into 2, the distribution of forage feed and the distribution of concentrate feed. PT Indo Prima Beef made 2 types of concentrates which named F8 and F9. F8 is a concentrate that has 20% protein content and 63% of energy (TDN). F8 concentrate was made for the grower period while F9 concentrate made for the finisher period. F9 has a higher energy content (TDN) of 69% and a lower protein content of 18%. Keywords: beef cattle, feed, management